Shaka: a new and novel processing technology to produce commercially sterile canned foods. - Angalet, Stephanie Marie (Kansas State University, 2011)
The process of canning or “commercial sterilization” has been studied for more than two centuries. The first to develop canning as a defense against spoilage was Nicholas Appert also known as the “father of canning.” Appert invented a method of preservation by enclosing food in hermetically sealed containers and then heating containers to boiling temperatures for a specific period of time. The canning preservation method has changed over the years, and continues to change for the better. Technology for retorts, or processing vessels, has grown from the traditional steam heating medium to also include water and steam/water spray heating mediums. The once static vessels, now utilize rotation and shaking motions to decrease process time and in turn increase product quality. The product packaging has also evolved to include not only rigid metal containers, but semi-rigid and flexible plastic containers. The variety of packaging adds greater flexibility to the type of food products that can be produced in a shelf stable manner. Canning or “commercial sterilization” is still used today by the food industry as a method of providing safe food with extended shelf life. Today’s goal of commercial sterilization is to continue to produce safe food products that are high in quality and profitable to produce. A variety of processing equipment is available to accomplish those goals, ranging from a basic steam retort to the newest technology on the market known as Shaka. This new retort technology uses reciprocal agitation to shorten processing times and increase the quality of the final products. Studies have shown that the Shaka process reduces processing times better than 20-fold compared to a still process and better than 10-fold compared to a rotary process. As the field of thermal processing continues to evolve, the challenge will be to consistently produce safe, commercially sterile food that exceeds current quality expectations in a shorter process time while using less energy. Shaka, and other new technologies, will help the food industry meet these challenges and expectations by expanding the current capabilities of thermal processing to meet consumer demands.
Keywords: Thermal processing; Shaka; Retorts; Canning; Food Science (0359)